2003
DOI: 10.1542/peds.111.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Social Competencies of Adolescents Who Were Extremely Low Birth Weight

Abstract: This study is unique in the inclusion of both parent and teen self-report of behaviors. Significant differences were apparent only by parent report for ADHD and depression among ELBW teens. Significant predictors of behavioral scores for parents include group, gender, family function, developmental quotient, maternal mood, and socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
154
4
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(185 citation statements)
references
References 52 publications
20
154
4
7
Order By: Relevance
“…Follow-up studies have shown that these children are often confronted with developmental problems and psychiatric diagnoses in late childhood and early adolescence (2)(3)(4)(5)(6)(7)(8)(9). Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies have shown that these children are often confronted with developmental problems and psychiatric diagnoses in late childhood and early adolescence (2)(3)(4)(5)(6)(7)(8)(9). Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond somatic growth, IUGR also impacts brain development, thus increasing the risk for later neurological complications (24). In the present study, we focused our attention on brain hippocampal metabolism and gene expression at PND7, a late neuronal proliferative phase in the rat, documenting for the first time alterations of this tissular development due to DEX-induced IUGR and the potential reversal of these alterations by bLf supplementation.…”
Section: Discussionmentioning
confidence: 98%
“…3 In case of missing data, authors were contacted. 5,28,32,[36][37][38] Some authors were not able to provide missing data 5,28 or could not be reached. 39 These studies, therefore, were not included in the meta-analysis.…”
Section: Behavioral Problemsmentioning
confidence: 99%
“…The incidence of major disabilities such as cerebral palsy, mental retardation, deafness, or blindness is fairly low. 1 There is growing awareness that the majority of nondisabled survivors encounter more "subtle" problems such as academic underachievement, 2 behavioral problems, [3][4][5] and deficits in higher-order neurocognitive functions: the so-called executive functions (EFs), 6 which persist throughout childhood and young adulthood. 1,4,7 However, great variability exists in the published results because of small numbers of participants, high attrition rates, and substantial variations in methods and study design.…”
mentioning
confidence: 99%